Altered circulating endothelial progenitor cells in patients with keloid. (30th June 2015) - Zhang, G.‐Y.; Wu, L.‐C.; Liao, T.; Chen, G.; Chen, Y.‐H.; Meng, X.‐C.; Wang, A.‐Y.; Chen, S.‐Y.; Lin, K.; Lin, D.‐M.; Gao, W.‐Y.; Li, Q.‐F.
Summary: Evidence has suggested that vascular endothelial growth factor (VEGF), a crucial growth factor in regulating endothelial progenitor cells (EPCs), plays a central role in keloid formation. However, the levels of circulating EPCs in patients with keloid have not yet been explored. The aim of this study was to determine the number of circulating EPCs in patients with keloid. Circulating EPCs (defined as CD45− CD34+CD133+VEGFR2+cells) and VEGF levels from 39 patients with keloid and 22 healthy controls (HCs) were assessed by flow cytometry and ELISA, respectively. EPCs were detectable in the peripheral blood of patients with keloid. The number of circulating EPCs and the levels of plasma VEGF were significantly higher in patients with keloid than in HCs. However, no correlation was found between the number of circulating EPCs and the serum VEGF levels. This study provides the first evidence that EPCs are increased in the peripheral blood of patients with keloid. Understanding the roles of EPCs in keloid fromation may lead to the development of novel therapeutic strategies for keloid.